The Evolutions of Romanian ‘Historians´ Front’ during Stalinism and Late Socialism. RCP’s Plans for Establishing a Central Institute for National History - VELIMIROVICI, Felician (Studia Universitatis Babeș-Bolyai Historia, 2015)
To examine the evolutions of Romanian ‘historians’ front’ during Stalinism and Late Socialism in a short study might seem presumptuous, but the following pages do not pretend to offer a full-scale exegesis of the practices of doing and using the discours(es) of history in Communist Romania. Rather, I have chosen to discuss here the metamorphoses of this crucial concept between 1948 and 1985, by analyzing its origins, significance and manners into which it has been actively engaged in the Stalinist and Ceauşescuist broader ideological framework by different social agents. The first part of my study focuses upon the ways in which party propagandists and historians have publicly used the ‘historians’ front’ formula during our ‘cultural revolution’ and the following years. In the second section of my interpretation I present, by exploiting a wealth of previously inaccessible archival sources, the Romanian Communist Party’s concrete plans and preparations to materialize this Stalinist concept by creating a single and unique Central Institute for National History. I argue that, under Nicolae Ceauşescu, the party has constantly tried to bring national history-production process under a more and more firmer political control.